Mapping the Evolution of Ethical Dimension on Artificial Intelligence Research through Co-word Analysis - Susanto, Ari; Amin, Khoirul; Putra, M Tri Media (Proceeding International Conference on Religion, Science and Education, 2024)
Artificial Intelligence (AI) has experienced very rapid development in the last few decades. Apart from that, AI has and will change many aspects of human life. However, as AI technology continues to develop, questions arise in the ethical dimension related to how ethically we as humans interact in utilizing or using Artificial Intelligence (AI). Therefore, this research aims to explore the extent to which research related to ethical dimensions in relation to the use of AI has been carried out. This research will use a bibliometric approach, specifically in Co-word analysis to identify core research themes and trends related to ethical dimensions in the use of Artificial Intelligence (AI). The results of this research are: 1) the research on the ethical dimension in AI has been massively discussed. It can be seen from the total number of occurrences of the words "artificial intelligence" and "ethics" that reach 1608 and 1223 times. 2) there are 4 clusters where each cluster consists of 155, 28, 19 and 19 keywords. The biggest keyword is "artificial intelligence" with 1608 total accuracy and 3964 link strength, followed by the word "ethic" with 1223 total accuracy and 3180 total accuracy 3) in the Evolution of the words Artificial Intelligence and the word Ethics are still often mentioned to this day and have given rise to other words related to the two such as the words AI ethics, Ethics of AI, Machine Ethics, artificial Intelligence ethics etc. 4) the words "information technology" and "decision-making" which are in the Niche themes quadrant on the thematic map graphic indicate that although this theme has experienced an increase in interest, not much research has been conducted regarding this theme.